Therapeutic potential of a choline-zinc-vitamin E nutraceutical complex in ameliorating thioacetamide-induced nonalcoholic fatty liver pathology in zebrafish. - Bingbing Cao; Jiali Zhou; Bo Xia; Xiaoqing Li; Rui Wang; Yiqiao Xu; Chunqi Li (PLoS ONE)
Choline has been proven to be effective in maintaining liver function. However, the effect of choline, in combination with other nutrients, on the improvement of non-alcoholic fatty liver disease (NAFLD) remains unclear. This study aimed to investigate the potential effect of the nutraceutical complex containing choline bitartrate, zinc citrate, and dl-α-Tocopheryl acetate on NAFLD in the zebrafish model. The NAFLD model was induced in zebrafish by administering thioacetamide. Experimental groups were established, including a normal control group, the model control group, the positive control group, the nutraceutical complex intervention group, and the choline bitartrate alone intervention group. The intervention was administered to the zebrafish in a water-soluble form, while the positive control group received polyene phosphatidylcholine at a concentration of 50.0 μg/mL. Notably, the protective effect of the nutraceutical complex against NAFLD is more pronounced than that observed with choline bitartrate supplementation alone. The results of transcriptomics and quantitative real-time PCR showed that the potential mechanisms underlying the effects of the nutraceutical complex might involve the upregulation of acacia, acsl1a, fbp2 gene expression, and the downregulation of tbc1d1 gene expression. These results were further validated by western blotting and overexpression experiments. Our findings indicated that choline bitartrate, zinc citrate, and dl-α-Tocopheryl acetate can help improve NAFLD. The results of this study provide evidence for the application of the nutraceutical complex in the improvement of NAFLD.